Analisis Komparasi Kinerja Keuangan Sebelum dan Sesudah Merger Pada Bank Syariah Indonesia (BSI) Menggunakan Metode Economic Value Added (EVA) dan Market Value Added (MVA) - Alya Jilana, Zikra; Pratiwi, Windi (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2024)
This Islamic bank merger has a strategy, namely as a corporate action or an action taken which aims to achieve the company's desired targets and is able to increase value for stakeholders and have a positive impact on shareholders. So, if financial performance changes, these changes can be used to assess whether the merger will have a good impact on the company or not. One tool for measuring financial performance to see the level of management's success in managing the financial resources owned by the company is to use EVA and MVA. The method used in this research is the EVA, MVA and Paired Sample T-Test approaches. Where the Paired Sample T-Test is used to test two averages from two independent samples. From the results of research using the EVA and MVA methods it can be seen that the EVA and MVA of PT. Bank Syariah Indonesia, Tbk has a positive value. A positive EVA indicates that there is added value to the company, indicating the company's performance and a positive MVA indicates that the company management has succeeded in increasing the value of the company with the capital that has been invested by capital owners or investors. The difference in financial performance using the Paired Sample T-Test test at Bank Syariah Indonesia, there is a significant difference in financial performance which is smaller than the alpha value (0.000 < 0.05).